Bilateral ovarian cysts of mature cystic teratoma and Endometrioma: Its surgical challenges and review of literature. Issue 3 (September 2021) - Bindra, Vimee; Reddy, Mamatha; Mohanty, Girija Shankar; Agarwal, Neha; Kulkarni, Aditya
Teratomas are most frequent germ cell tumors of ovary with an incidence of 15%–20% of all ovarian neoplasm while endometriomas are present in 25.5%–45% of women with pelvic endometriosis. In spite of their increased individual incidence, association of cystic teratomas and ovarian endometriomas is extremely rare. Our case is that of a 33-year-old nulligravida who presented with heavy menstrual flow and pain during periods for last few months, ultrasonography revealed 74 × 57 mm mass in right adnexa-likely ovarian dermoid, enlarged left ovary with two small cysts of size 33 × 29 mm and 25 × 20 mm likely endometrioma, managed by laparoscopy, found to have left ovarian endometrioma of 6 × 6 cm and right ovarian dermoid cyst of 10 × 8 cm size, histopathology confirmed the same. This association of teratoma in one ovary and endometrioma in other ovary of same patient poses a surgical challenge, when it affects young and nulliparous women. Further follow up is mandatory for this simultaneous finding of ovarian endometriosis with coincidental dermoid cyst to assess ovarian reserve, recurrence of either of the cysts, and it also presents a challenge to clinicians to predict the post-operative course of such cases.